Thumbelina: favourite tales - Daly, Audrey; Stone, Petula Andersen, H. C. (Ladybird London, 1993)
A tiny girl no bigger than a thumb is stolen by a great ugly toad and subsequently has many adventures and makes many animal friends, before finding the perfect mate in a warm and beautiful southern land